Anti-Space: the political complexion of an inner city art gallery - Vickery, Jonathan P. (Journal of Architecture and Urbanism, 2014)
The subject of this paper is an inner city artist-run gallery called Eastside Projects. As part of an historical trend in artistrun spaces, Eastside Projects have innovated a strategic approach to post-industrial space, their location and role within the city of Birmingham, UK. This paper outlines their approach in the context of the recent cultural policy frameworks impressed on publicly funded city-based art organisations. It attempts to extend the conceptualisation of contemporary art in the city within urban studies generally, specifically investigating the theoretical potential of Eastside Project’s curatorial strategy. How can we define public agency for art in the neoliberal city? For Eastside Projects, agency is defined principally through space and the aesthetics of space. This paper proposes a theoretical framework for articulating the political aesthetics of new public spaces for art.